Adaptive model predictive control of autonomic distributed parallel computations with variable horizons and switching costs - Mencagli, G. (Concurrency and computation, 2016)
Summary Autonomic computing is a paradigm for building systems capable of adapting their operation when external changes occur, such as workload variations, load surges and changes in the resource availability. The optimal configuration in terms of the number of computing resources assigned to each component must be automatically adjusted to the new environmental conditions. To accomplish the execution goals with the desired Quality of Service, decision‐making strategies should be in charge of selecting the best reconfigurations by taking into account metrics like performance, efficiency (avoiding wasting resources), number and frequency of reconfigurations, and their amplitude (performing minimal modifications of the current configuration). This paper presents a decision‐making strategy that merges the potential of Model Predictive Control with a cooperative optimization framework. After a description of our approach, we investigate the effect of different switching costs to model the resource allocation problem. We use a control method in which our proactive decision‐making strategy (designed to use future prediction horizons) is made adaptive itself by dynamically changing the horizon length on the basis of the prediction errors. Simulations have been used to exemplify our approach and to discuss the effectiveness of the variable‐horizon strategy in achieving the best trade‐offs between reconfiguration metrics. Copyright © 2015 John Wiley & Sons, Ltd.